2009
DOI: 10.4156/jdcta.vol3.issue4.13
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Motor Imagery EEG Signals Based on Time–Frequency Analysis

Abstract: We describe a new technique for the classification of motor imagery electroencephalogram (EEG) recordings. The technique is based on a time-frequency analysis of EEG signals, regarding the relations between the EEG data obtained from the C3/C4 electrodes, the features were reduced according the Fisher distance. This reduced feature set is finally fed to a linear discriminant for classification. The algorithm was applied to 3 subjects, the classification performance of the proposed algorithm varied between 70% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Thus, the one-dimensional feature in the time domain is expanded to two-dimensional features in the time-frequency domain. Past studies have shown that the frequency feature plays an important role in BCI detection [14] , [35] , [43] , [44] . Our method expands time features to time and frequency features, allowing more feature vectors to be used in feature detection.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the one-dimensional feature in the time domain is expanded to two-dimensional features in the time-frequency domain. Past studies have shown that the frequency feature plays an important role in BCI detection [14] , [35] , [43] , [44] . Our method expands time features to time and frequency features, allowing more feature vectors to be used in feature detection.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of filter is possible for sharpest roll-off and equi-ripple in pass and stop band that can be varied accordingly. The pass band frequency of the filter is selected due to the presence of motor imagery signals in theta (3-7 Hz), alpha (7-13 Hz) and beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) [21] frequency bands.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…Last is the selection of a special type of recurrent neural network, where the correct intended classes represent the stable points on the minima of Lyapunov surface designed for the neural network. The choice of the neural network classifier is made because of extensive use in motor imagery classification [17], [18] and of course our background [19], [20].…”
Section: Introductionmentioning
confidence: 99%
“…While multi-channel electroencephalogram (EEG) signals offer enhanced spatial resolution [12], they also introduce unwanted noise interference and redundant information [13]. An effective channel selection method can mitigate this issue by eliminating channels containing noise signals and retaining those correlated with the activation patterns of specific brain regions [14].…”
Section: Introductionmentioning
confidence: 99%